Dexamethasone‐mediated inhibition of Notch signalling blocks the interaction of leukaemia and mesenchymal stromal cells. (18th November 2021) - Ahmed, Helal Mohammed Mohammed; Nimmagadda, Subbaiah Chary; Al‐Matary, Yahya S.; Fiori, Maren; May, Tobias; Frank, Daria; Patnana, Pradeep Kumar; Récher, Christian; Schliemann, Christoph; Mikesch, Jan‐Henrik; Koenig, Thorsten; Rosenbauer, Frank; et al.
Summary: Acute myeloid leukaemia (AML) is a haematological malignancy characterized by a poor prognosis. Bone marrow mesenchymal stromal cells (BM MSCs) support leukaemic cells in preventing chemotherapy‐induced apoptosis. This encouraged us to investigate leukaemia‐BM niche‐associated signalling and to identify signalling cascades supporting the interaction of leukaemic cells and BM MSC. Our study demonstrated functional differences between MSCs originating from leukaemic (AML MSCs) and healthy donors (HD MSCs). The direct interaction of leukaemic and AML MSCs was indispensable in influencing AML cell proliferation. We further identified an important role for Notch expression and its activation in AML MSCs contributing to the enhanced proliferation of AML cells. Supporting this observation, overexpression of the intracellular Notch domain (Notch ICN) in AML MSCs enhanced AML cells' proliferation. From a therapeutic point of view, dexamethasone treatment impeded Notch signalling in AML MSCs resulting in reduced AML cell proliferation. Concurrent with our data, Notch inhibitors had only a marginal effect on leukaemic cells alone but strongly influenced Notch signalling in AML MSCs and abrogated their cytoprotective function on AML cells. In vivo, dexamethasone treatment impeded Notch signalling in AML MSCs leading to a reduced number of AML MSCs and improved survival of leukaemic mice. In summary, targeting the interaction of leukaemic cells and AML MSCs using dexamethasone or Notch inhibitors might further improve treatment outcomes in AML patients.